1996
DOI: 10.1159/000188908
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Glomerular and Serum lgA1 to Jacalin in IgA Nephropathy

Abstract: To analyze O-linked oligosaccharides (O-glycans) in the hinge region of IgAl in IgA nephropathy (IgAN), the reactivity of IgA1 to jacalin, which specifically binds to O-glycans, was investigated. Initially, renal biopsy specimens from 5 patients with IgAN and 3 patients with other renal diseases were investigated in an immunofluorescence study with jacalin, monoclonal antihuman IgAl and IgA2 antibodies. All of the renal biopsy specimens of IgAN and none of other renal diseases were positively stained by both F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…There have been many reports on the presence of an incompletely glycosylated O-linked oligosaccharide(s) on the IgA1 hinge region in some IgAN patients [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Previously, we confirmed that enzymatically under-glycosylated IgA1 accumulated in rat glomeruli [20].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…There have been many reports on the presence of an incompletely glycosylated O-linked oligosaccharide(s) on the IgA1 hinge region in some IgAN patients [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Previously, we confirmed that enzymatically under-glycosylated IgA1 accumulated in rat glomeruli [20].…”
Section: Discussionmentioning
confidence: 55%
“…Further, human IgA1 molecules have a unique glycosylated hinge that possesses O-glycan side chains [3]. There are many reports on the presence of an incompletely glycosylated O-linked oligosaccharide(s) in the IgA1 hinge region in some IgAN patients [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Such microheterogeneity of a glycoprotein is a well-known phenomenon (26). However, the importance of the structure of the hinge portion of IgA1 should not be ignored because of the relationship with IgA nephropathy and because incompleteness of a sugar chain on the hinge portion would be related to the stability of the IgA1 molecule and the self-aggregation of IgA1 (5)(6)(7)(8)(17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…To detect the SV40 T antigen, an antibody against SV40 T antigen, obtained from Bethyl Laboratories (Montgomery, TX, USA) was used. In cytoimmunochemistry analysis was performed basically as described elsewhere [5] using the same anti-aB-crystallin peptide sera. LECs from passage 30 were grown on a chamber slide until a monolayer had formed for immunocytochemical analysis.…”
Section: Ascorbic Acid Transport Activity and Rt-pcr Analysis Of Svctsmentioning
confidence: 99%